The multiple-mechanisms hypothesis of biodiversity–stability relationships - Eisenhauer, Nico; Mueller, Kevin; Ebeling, Anne; Gleixner, Gerd; Huang, Yuanyuan; Madaj, Anna-Maria; Roscher, Christiane; Weigelt, Alexandra; Bahn, Michael; Bonkowski, Michael; Brose, Ulrich; Cesarz, Simone; et al. (Basic and applied ecology, 2024)
Long-term research in grassland biodiversity experiments has provided empirical evidence that ecological and evolutionary processes are intertwined in determining both biodiversity–ecosystem functioning (BEF) and biodiversity–stability relationships. Focusing on plant diversity, we hypothesize that multifunctional stability is highest in high-diversity plant communities and that biodiversity–stability relationships increase over time due to a variety of forms of ecological complementarity including the interaction with other biota above and below ground. We introduce the multiple-mechanisms hypothesis of biodiversity–stability relationships suggesting that it is not an individual mechanism that drives long-term biodiversity effects on ecosystem functioning and stability but that several intertwined processes produce increasingly positive ecosystem effects. The following six mechanisms are important. Low-diversity plant communities accumulate more plant antagonists over time (1), and use resources less efficiently and have more open, leaky nutrient cycles (2). Conversely, high-diversity plant communities support a greater diversity and activity of beneficial interaction partners across trophic levels (3); diversify in their traits over time and space, within and across species, to optimize temporal (intra- and interannual) and spatial complementarity (4), create a more stable microclimate (5), and foster higher top-down control of aboveground and belowground herbivores by predators (6). In line with the observation that different species play unique roles in ecosystems that are dynamic and multifaceted, the particular mechanism contributing most to the higher performance and stability of diverse plant communities might differ across ecosystem functions, years, locations, and environmental change scenarios. This indicates “between-context insurance” or “across-context complementarity” of different mechanisms. We introduce examples of experiments that will be conducted to test our hypotheses and which might inspire additional work.